2023
DOI: 10.15252/embj.2022112559
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N‐methyltransferase sustains a core epigenetic program that promotes metastatic colonization in breast cancer

Abstract: Metastatic colonization of distant organs accounts for over 90% of deaths related to solid cancers, yet the molecular determinants of metastasis remain poorly understood. Here, we unveil a mechanism of colonization in the aggressive basal-like subtype of breast cancer that is driven by the NAD + metabolic enzyme nicotinamide N-methyltransferase (NNMT). We demonstrate that NNMT imprints a basal genetic program into cancer cells, enhancing their plasticity. In line, NNMT expression is associated with poor clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…[17,18] More recently, Joana et al reported that NNMT sustains a core epigenetic program that promotes metastatic colonization in breast cancer. [44] Our current study revealed that NNMT is a critical promoter of breast cancer cell proliferation and cell cycle progression, providing additional evidence for the role of NNMT in promoting breast cancer progression.…”
Section: Discussionsupporting
confidence: 64%
“…[17,18] More recently, Joana et al reported that NNMT sustains a core epigenetic program that promotes metastatic colonization in breast cancer. [44] Our current study revealed that NNMT is a critical promoter of breast cancer cell proliferation and cell cycle progression, providing additional evidence for the role of NNMT in promoting breast cancer progression.…”
Section: Discussionsupporting
confidence: 64%
“…Other methyltransferases can impact epigenetics by either altering the concentration of the methyl donors or creating a metabolic methylation sink. An example of this is the enzyme Nicotinamide N-methyltransferase (NNMT) which promotes epigenetic remodeling in breast cancer and affects all other NAD+ dependent enzymes such as poly-ADP ribose polymerases (PARPs) and sirtuins [10,11]. In addition, research has been performed using combinations of various dietary phytochemicals that induce inhibition of these silencing enzymes to analyze a decrease in the growth of cancerous cell lines [12].…”
Section: Introductionmentioning
confidence: 99%